CHINESE PUBLIC DIPLOMACY TOWARDS AFRICA IN THE CHINA GLOBAL TELEVISION NETWORK (CGTN) 2016-2020 - Ilma Zakia; Den Yealta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACT China seeks greater engagement with Africa, increasing its potential to shape narratives in a persuasive way that can support its image or interests abroad. This research focuses on the CGTN in Africa as China's flagship effort to win the hearts and minds of the people in the African Region. The momentum is marked by the establishment of a CGTN production center in Nairobi, Kenya in January 2011. This research built theoretically using a constructivist perspective and is supported by the theory of public diplomacy. The formulation of all arguments, data, facts, and theoretical framework in this study uses a qualitative description method. This study also uses the nation-state as a level of analysis. The result of this research conclude that China is making efforts to form a positive image in the African Region by utilizing CGTN, as one of the media owned by the government. China uses CGTN as a soft power instrument in conveying ideas, values and culture; conducting public diplomacy by involving CGTN as a supporting actor for public diplomacy activities; as well as using CGTN to sway African public opinion about China. Keywords: CGTN, Public Diplomacy, African Region, foreign policy, China-Africa relations